1993
DOI: 10.1038/363347a0
|View full text |Cite
|
Sign up to set email alerts
|

Induction of LTP in the hippocampus needs synaptic activation of glutamate metabotropic receptors

Abstract: Understanding the mechanisms of long-term potentiation (LTP) should provide insights into the molecular basis of learning and memory in vertebrates. Ionotropic glutamate receptors play a central role in LTP; AMPA (alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionate) receptors and NMDA (N-methyl-D-aspartate) receptors mediate synaptic responses that are enhanced in LTP and, in addition, NMDA receptors are necessary for the induction of LTP in most pathways. There is also circumstantial evidence that metabotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
275
3
4

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 703 publications
(297 citation statements)
references
References 33 publications
15
275
3
4
Order By: Relevance
“…Thus, there is a clear-cut difference between interneuron subtypes that exhibit rhythmic firing (I and II) versus those that do not (III and IV), with frequent mGluR1 expression in the former and rare expression in the latter two classes. This observation is of particular interest in view of previous data indicating that the contribution of mGluRs to excitatory responses is significant only after activation by highfrequency stimuli (Bashir et al, 1993;Miles and Poncer, 1993). The evidence for the preferential extrasynaptic localization of mGluRs (Baude et al, 1993) is also indicative for a functional role of these glutamate receptors under conditions of highfrequency stimulation.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, there is a clear-cut difference between interneuron subtypes that exhibit rhythmic firing (I and II) versus those that do not (III and IV), with frequent mGluR1 expression in the former and rare expression in the latter two classes. This observation is of particular interest in view of previous data indicating that the contribution of mGluRs to excitatory responses is significant only after activation by highfrequency stimuli (Bashir et al, 1993;Miles and Poncer, 1993). The evidence for the preferential extrasynaptic localization of mGluRs (Baude et al, 1993) is also indicative for a functional role of these glutamate receptors under conditions of highfrequency stimulation.…”
Section: Discussionmentioning
confidence: 63%
“…This has previously been reported by some groups (Bashir et al, 1993;Bortolotto et al, 1995;Richter-Levin et al, 1994;Riedel et al, 1995), and not by others (Chinestra et al, 1993;Manzoni et al, 1994;Selig et al, 1995). Also work from mGluR5 knockout mice have shown that NMDA-receptor mediated LTP is impaired in these animals (Jia et al, 1998;Lu et al, 1997).…”
Section: Discussionmentioning
confidence: 80%
“…The involvement of the mGluRs in hippocampal LTD has been well established (Bolshakov and Siegelbaum, 1994;Fitzjohn et al, 1999;O'Mara et al, 1995;Snyder et al, 2001), however their contribution to LTP has been a subject of unresolved debate (Bashir et al, 1993;Bortolotto et al, 1995;Chinestra et al, 1993;Manzoni et al, 1994;Richter-Levin et al, 1994;Riedel et al, 1995;Selig et al, 1995). To date, eight mGluR subtypes, designated mGluR1 to mGluR8, have been cloned from the mammalian brain.…”
Section: Introductionmentioning
confidence: 99%
“…The study of hippocampal LTP has been a preferred experimental model due to the planar arrangement of the Schaffer collateral pathways leading to the CA1 region of the hippocampus. The induction of LTP in the CAI region of the hippocampus typically involves the activation of NMDA and metabotropic glutamate receptors, which increase intracellular calcium concentration [3][4][5][6]. Stimulation of these glutamate receptors promotes the activation of phospholipase A2 leading to the release of arachidonic acid [7,8] and the initiation of PAF synthesis.…”
Section: Introductionmentioning
confidence: 99%